Perinatal exposure to atazanavir-based antiretroviral regimens in a mouse model leads to differential long-term motor and cognitive deficits dependent on the NRTI backbone - Dhume, Shreya H.; Balogun, Kayode; Sarkar, Ambalika; Acosta, Sebastian; Mount, Howard T. J.; Cahill, Lindsay S.; Sled, John G.; Serghides, Lena (Frontiers in Molecular Neuroscience, 2024)
Background: Combination antiretroviral therapy (ART) use in pregnancy has been pivotal in improving maternal health and reducing perinatal HIV transmission. However, children born HIV-exposed uninfected fall behind their unexposed peers in several areas including neurodevelopment. The contribution of in utero ART exposure to these deficits is not clear. Here we present our findings of neurocognitive outcomes in adult mice exposed in utero to ART. Methods: Dams were treated with a combination of ritonavir-boosted atazanavir with either abacavir plus lamivudine (ABC/3TC+ATV/r) or tenofovir disoproxil fumarate plus emtricitabine (TDF/FTC+ATV/r), or water as a control, administered daily from day of plug detection to birth. Offspring underwent a battery of behavioral tests that investigated motor performance and cognition starting at 6-weeks of age and ending at 8 months. Changes in brain structure were assessed using magnetic resonance imaging and immunohistochemistry. Expression of genes involved in neural circuitry and synaptic transmission were assessed in the hippocampus, a region strongly associated with memory formation, using qPCR. Findings: Pups exposed to TDF/FTC+ATV/r showed increased motor activity and exploratory drive, and deficits in hippocampal-dependent working memory and social interaction, while pups exposed to ABC/3TC+ATV/r showed increased grooming, and deficits in working memory and social interaction. Significant volumetric reductions in the brain were seen only in the ABC/3TC+ATV/r group and were associated with reduced neuronal counts in the hippocampus. Altered neurotransmitter receptor mRNA expression as well as changes in expression of the neurotrophic factor BDNF and its receptors were observed in both ART-exposed groups in a sex-dependent manner. Interpretation: In our model, in utero ART exposure had long-term effects on brain development and cognitive and motor outcomes in adulthood. Our data show that neurological outcomes can be influenced by the type of nucleoside reverse transcriptase inhibitor backbone of the regimen and not just the base drug, and display sex differences.